ECHOCARDIOGRAPHY PATTERNS OF MYOCARDIAL PATHOLOGY IN CHILDREN WITH JUVENILE ARTHRITIS - A. B. Sugak; E. I. Alekseeva; I. V. Dvoryakovsky (Российский кардиологический журнал)
Juvenile rheumatoid arthritis (JRA) and juvenile spondiloarthritis (JSA) are chronic auto-immune disorders, characterised by various extraarticular pathology, including heart pathology. The most available non-invasive method for diagnosing asymptomatic myocardial pathology is echocardiography. The study included 185 children with JRA and 43 children with JSA. The systemic JRA variant was characterised by high prevalence of left ventricular (LV) hypertrophy (48,2%), LV dilatation (32,9%), and LV diastolic dysfunction (30,6%) with unaffected systolic function. The respective percentages in the arthritic JRA variant were 11%, 13%, and 15%, which pointed to the need for follow-up and possible diagnosis revision, due to systemic character of the disease. In JSA, reduced total LV contractility was the most prevalent sign (27,9%). To identify the reasons for the latter, further detailed examination was necessary.